POST-HARVEST LOSSES OF ONION CULTIVATION IN KALABURAGI, KARNATAKA - S. BONDITA (The Journal of Research ANGRAU, 2023)
The empirical field study was conducted during 2021to understand the Agri-logistics and Postharvest Losses (PHLs) of crops in the Kalaburagi district of Karnataka.The findings of the study indicated that the loss due to logistics was more for the farmers compared to the field-level loss. In onion cultivation, there was only quantitative lossandno quality loss. The monetary loss of onions was around Rs.40,000 per acre—the loss of onions due to logistics to the farmer was around Rs. 34,000 per acre. After harvest, the loss wasdue to the lack of inefficient logistics compared to other factors. Post-harvest losses of agricultural produce indicatedthe inefficiency of post-harvest management. In mitigating PHLs, effective logistics services are desirable, and their sustainability is equally important.